PERILAKU BULLYING SISWA DILINGKUNGAN SMP NEGERI 4 GERUNG KABUPATEN LOMBOK BARAT - muliana; Muhammad Mambrur Haslan S.pd M,Hum; Sawaludin, S.Pd.,M.Pd; Bagdawansyah Alqadri, S.Pd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the types of bullying at SMP Negeri 4 Gerung, Lombok Barat, and how teachers handle it. Using a qualitative, descriptive approach, data were gathered through interviews, observation, and documentation. The main informant was the guidance counselor, alongside the principal, vice principal of student affairs, and PPKn teachers. The findings identified three main bullying types: verbal, physical, and social, with verbal bullying being the most common. Physical bullying includes pushing, hair-pulling, and forcibly taking belongings. Social bullying involves exclusion from groups, gossiping, and mocking based on students’ background. Bullying cases lead to psychological pressure, fear, withdrawal, and decreased motivation to learn. Based on data from the guidance counselor in 2024, there were 4 reported bullying cases involving 17 victims. Teachers’ efforts to address bullying are carried out through preventive, repressive, and curative approaches by involving teachers, parents, and the school principal. Comprehensive and continuous intervention is essential to establish a safe and child-friendly school environment.